Building planning and construction - International Code Council ([Birmingham, Alabama] : International Code Council, 2003)
Discusses the code provisions of the International Residential Code involving building, planning, and construction. Chapter 3 of the IRC discusses items that relate to fire and life safety, environmental issues such as natural light and ventilation
Title from title screen
The title is from chapter three of the International Residential Code (IRC)
Hosts: Martha Weaver, Asot Hoke
DVD format
Keywords: Building laws -- United States; Building inspection -- United States; Dwellings -- United States